Suspension protoplasts as useful experimental tool to study localization of GFP-tagged proteins in Arabidopsis thaliana - Rigó, Gábor (Acta Biologica Szegediensis, 2008)
A routinely used protocol is described here including protoplast isolation and PEG-mediated plasmid DNA transformation followed by LSM analysis. We have isolated protoplasts from suspension cultures of wild-type Arabidopsis thaliana Col-0, than protoplasts were transformed with different constructs of AtCRK5 gene tagged with GFP. The protoplast isolation and PEG-mediated transformation process took 6-8 hours. Localization studies could be carried out by LSM microscopy in 0-24 hrs followed transformation. Using this method, we could have localized both 35S::cCRK5-GFP and g::gCRK5-GFP fusion proteins in plasma membrane of cell suspension originated protoplasts, while an N-terminal myristoylation site masked version of 35S::cCRK5-GFP and the N-terminal GFP tagged 35S::GFP-cCRK5 fusion proteins could be found in cell nuclei. Mislocalization of the two last fusion proteins is in good agreement with the fact that the N-terminal myristoylation sites of these proteins were impaired. As a conclusion, the Arabidopsis suspension derived protoplast system is very quick tool for identification of protein localization and to provide possibility to obtain preliminarily information on possible protein localization prior to plant regeneration.